PWE-104 The Financial Impact Of A Nurse-led Ibd (inflammatory Bowel Disease) Telephone Advice Service, In A Large District General Hospital. (9th June 2014) - Squires, S; Boal, A; Naismith, G
Abstract : Introduction: It has become increasingly recognised that outpatient management is more cost effective in IBD. 1 IBD Standards (Revised 2013) recommend telephone advice for patients with regards to symptoms and medication management. This report attempts to quantify the net financial impact of this service at our hospital since it was introduced in August 2013. Methods: The Royal Alexandra Hospital in Paisley is a District General Hospital with a catchment population of 200, 000 2 with approximately 2500 IBD patients. Data relating to the use of the Telephone Advice service was prospectively recorded on a daily basis for a period of 5 months. We Documented reasons for calling and the likely action taken by the patient had the telephone advice line not been available. Cost savings based on alternative outcomes were made in accordance the Department of health figures. 3 Results: The mean calls per month was was 88 [IQR 24] – (Mean calls which were deemed Non-IBD issues was, was 30 calls per month [IQR 8.0]) The mean cost of staffing the IBD advice line with an IBD Clinical Nurse Specialist was £482.00 per month [IQR 195.5]. The mean time spent on calls per month was 28.5 h [IQR 11.5]. Cost Savings over 5 months for avoidance of GP consultation was £3408.00. Savings for avoidance of a consultant appointment made over the 5 month period was £27454.00. Savings made from patients avoiding either an A+E or Hospital Admission were £540.00 and £11488.00 respectively over the 5 month period. The net saving was £42890.00. Conclusion: A Nurse-Led telephone advice line appears to be a cost effective intervention. It may prevent patients from unnecessary hospital attendance. Savings can be made to both primary and secondary care. Overall, it appears that the advice line is providing a highly valuable service, not just in terms of accessible treatment decisions and guidance for patients, but cost savings when Specialist Nurse time is compared to General Practitioners, Consultants or hospital facilities. References: Park KT, Bass D. Inflammatory bowel disease‐attributable costs and cost‐effective strategies in the United States: A review. Inflammatory Bowel Diseases, 2011 – Wiley Online Library NHSGGC (National Health Service, Greater Glasgow and Clyde) – Consultation document 2006-2012 http://www.nhsggc.org.uk Department of Health reference Costs 2011–2012 https://www.gov.uk Disclosure of Interest: None Declared.